Pengaruh Kesadaran Wajib Pajak, Pelayanan Fiskus, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi yang Melakukan Kegiatan Usaha dan Pekerjaan Bebas di Kota Samarinda - Brata, Januar Dio; Yuningsih, Isna; Kesuma, Agus Iwan (FORUM EKONOMI, 2017)
The number of tax payers is increase for years. But, it is not balanced with the level of tax compliance. The compliance problem becomes an obstacle in optimizing the tax revenue. This study examines the level of compliance of individual taxpayers conducting business and professional services in Samarinda by using several independent variables such as awareness of the taxpayer, the service tax authorities and tax penalties. The population of this study is individual taxpayers conducting business and professional services in Samarinda. Based on data from the KPP Pratama Samarinda, until July 2016 there were 35.445 individual taxpayers conducting business and free job retention. Sampling was done by incidental sampling method. The number of sample is 100 people. Primary data collection method used is a survey method using questionnaires media. Data analysis techniques used in this study is the technique of multiple regression analysis. Based on the results of the analysis undertaken concluded that awareness of the taxpayer, and tax penalties had significant and positive impact on taxpayer compliance. The service tax authorities had no significant and negative impact on taxpayer compliance.Keywords: Tax compliance, the taxpayer awareness, the service tax authorities and tax penalties.